(untitled) (INNOVATIVE ECONOMY, 2024)
Svynous I.V., Turzhanskyi V.A., Shepel T.P., Nikitchenko S.O. THE ECONOMIC CONTENT OF PRODUCTION COSTS IN THE SYSTEM OF ACCOUNTING AND ENTERPRISE MANAGEMENT Purpose. The aim of the article is to propose recommendations of a theoretical nature regarding the understanding of the concept of "production costs" in the accounting and management system of the enterprise based on the generalization of the research results. Methodology of research. The research is based on general scientific and philosophical methodologies of researching phenomena and processes in the accounting system. By using the epistemological method, it became possible to expand and specify the understanding of concepts and categories related to accounting and enterprise management. Through critical analysis, it was ensured that problems related to the accounting of economic entities were established. The development of the theory and methodology of accounting and management of business structures is based on the methods of scientific research, including analysis, synthesis, induction, deduction, abstraction, idealization and generalization. In addition, with the help of the comparative legal method, the legislation regulating the activities of economic entities and the improvement of accounting were investigated. Findings. It was established that the concepts of "expenses", "costs" and "cost price" are not synonymous. Expenses should be understood as the acquisition of resources, and the moment when the enterprise acquires ownership rights to the purchased resources may not coincide with the moment of payment for the resources – that is, the condition of payment for the purchased resources is not mandatory for the recognition of the fact of the purchase of resources as expenses. It was proven that production costs represent a fee for the possibility of conducting production (fee for the use of resources, services, works, etc.), which varies depending on the conditions of its implementation, which allows achieving the set goals (the main one of which in the conditions of market relations is profit maximization). The generalization of approaches to the definition of the concepts of costs and cost price made it possible to distinguish the following characteristic features: the cost of products and their cost price are interrelated categories, since their basis is based on the labour spent on the production of products. At the same time, the value is determined by the social costs of production, and the cost price is determined by individual costs and is an economic category of the enterprise level. In the economic sense, the cost price is a monetary expression of the enterprise’s expenses for production and sale of products. Originality. The approach to interpreting the concepts of "expenses", "costs", "cost price" is substantiated, which differs from those available in the literature in a more complete coverage of business transactions, eliminates contradictory signs and duplication of business transactions (when the sign of the purchase of materials and the occurrence of accounts payable is considered as a characteristic of the concepts of "expenses" and "costs" simultaneously). Refined definitions of these concepts will allow obtaining more accurate parameters of the cost function, increasing the adequacy of modelling of management decisions regarding the full loading of production facilities, costing control, motivation of personnel to achieve target cost indicators, and increase the quality of planning of resource costs. Practical value. The results of the conducted research can be used to increase the level of efficiency of enterprise cost management, which will ensure optimal use of material resources and live labour. Key words: expenses, costs, cost price, accounting, management.